Pengaruh Nilai Tukar Rupiah pada US Dollar, Tingkat Inflasi, Dan Suku Bunga Sertifikat Bank Indonesia Terhadap Penanaman Modal Asing - M. Fakhry Iskhaq; Ronny Malavia Mardani (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTTo generate an appropriate and profitable investment decision, investorsneed to forecast capital market changes. In doing the forecasting, investors needto analyze the macroeconomic changes that are and will happen. The observationof changes in some macroeconomic variables such as inflation, interest rates ofIndonesian bank certificates, the rupiah exchange rate against the dollar andreliable foreign investment can help investors in forecasting and makinginvestment decisions.High inflation and bank interest rates will cause the company's operatingexpenses to be heavier and will affect the financial performance of the businessentity. On the other hand, rising interest rates is a promising investmentopportunity for deposit investors. As exchange rate trends continue to rise,investors tend to shift their capital to the foreign exchange market, in the hope ofgaining a higher return than investing in stocks, otherwise the decline in foreignexchange rates will lead to an increase in investment in stocks. All this willultimately affect the interest of foreign investors in investing their capital.Data used as sample in this research is inflation data, interest rate of SBI,exchange rate of rupiah to US dollar, which is limited to data closing everyquarter during period between year 2012 until year 2016 which is 20 observation.The data is obtained from the Central Bureau of Statistics and Bank Indonesia.The type of this research is explanatory researce and the method of analysis usedis multiple regression to explain the influence between independent variable anddependent variable. The result of this research shows significant influence ofrupiah exchange rate and SBI interest rate, to foreign investment. While inflationhas no effect on Foreign Investment.